Intracerebral Hemorrhage: A Common yet Disproportionately Deadly Stroke Subtype - O'Carroll, Cumara B; Brown, Benjamin L; Freeman, W David (Mayo Clinic proceedings, 2021)
Spontaneous intracerebral hemorrhage (ICH) is a medical emergency and is disproportionately associated with higher mortality and long-term disability compared with ischemic stroke. The phrase "time is brain" was derived for patients with large vessel occlusion ischemic stroke in which approximately 1.9 million neurons are lost every minute. Similarly, this statement holds true for ICH patients due to a high volume of neurons that are damaged at initial onset and during hematoma expansion. Most cases of spontaneous ICH pathophysiologically stem from chronic hypertension and rupture of small perforating vessels off of larger cerebral arteries supplying deep brain structures, with cerebral amyloid angiopathy being another cause for lobar hemorrhages in older patients. Optimal ICH medical management strategies include timely diagnosis, aggressive blood pressure control, correction of underlying coagulopathy defects if present, treatment of cerebral edema, and continuous assessment for possible surgical intervention. Current strategies in the surgical management of ICH include newly developed minimally invasive techniques for hematoma evacuation, with the goal of mitigating injury to fiber tracts while accessing the clot. We review evidence-based medical and surgical management of spontaneous ICH with the overall goal of reducing neurologic injury and optimizing functional outcome.